Can We Predict How Earthworm Effects on Plant Growth Vary with Soil Properties? - Kam-Rigne Laossi; Thibaud Decaëns; Pascal Jouquet; Sébastien Barot (Applied and Environmental Soil Science)
Earthworms are usually assumed to enhance plant growth through different mechanisms which are now clearly identified. It is however difficult to determine their relative importance, and to predict a priori the strength and direction of the effects of a given earthworm species on a given plant. Soil properties are likely to be very influential in determining plant responses to earthworm activities. They are likely to change the relative strength of the various mechanisms involved in plant-earthworm interactions. In this paper, we review the different rationales used to explain changes in earthworm effect due to soil type. Then, we systematically discuss the effect of main soil characteristics (soil texture, OM, and nutrient contents) on the different mechanisms allowing earthworm to influence plant growth. Finally, we identify the main shortcomings in our knowledge and point out the new experimental and meta-analytical approaches that need to be developed. An example of such a meta-analysis is given and means to go further are suggested. The result highlights a strong positive effect size in sandy soil and a weakly negative effect in clayey soil.